Bioactive Phenolic Compounds From Agri-Food Wastes: An Update on Green and Sustainable Extraction Methodologies - Panzella, Lucia; Moccia, Federica; Nasti, Rita; Marzorati, Stefania; Verotta, Luisella; Napolitano, Alessandra (Frontiers in Nutrition, 2020)
Phenolic compounds are broadly represented in plant kingdom, and their occurrence in easily accessible low-cost sources like wastes from agri-food processing have led in the last decade to an increase of interest in their recovery and further exploitation. Indeed, most of these compounds are endowed with beneficial properties to human health (e.g. in the prevention of cancer and cardiovascular diseases), that may be largely ascribed to their potent antioxidant and scavenging activity against reactive oxygen species generated in settings of oxidative stress and responsible for the onset of several inflammatory and degenerative diseases. Apart from their use as food supplements or as additives in functional foods, natural phenolic compounds have become increasingly attractive also from a technological point of view, due to their possible exploitation in materials science. Several extraction methodologies have been reported for the recovery of phenolic compounds from agri-food wastes mostly based on the use of organic solvents such as methanol, ethanol, or acetone. However, there is an increasing need for green and sustainable approaches leading to phenolic-rich extracts with low environmental impact. This review addresses the most promising and innovative methodologies for the recovery of functional phenolic compounds from waste materials that have appeared in the recent literature. In particular, extraction procedures based on the use of green technologies (supercritical fluid, microwaves, ultrasounds) as well as of green solvents such as deep eutectic solvents (DES) are surveyed